Precaution and protection policies of urban ecosystem in the Iblea north eastern coast of Sicily - Caterina Cirelli; Leonardo Mercatanti; Enrico Domenico Nicosia; Carmelo Maria Porto (European Regional Science Association (ERSA), 2005)
According to the hypothetical urban scenarios in the future, the urban ecosystem will be the piace where the most part of people live, with a deep negative impact on the world ecosystem. So it is necessary for all the people to get better ways of life in the towns and less and less unbalanced urban space, that to say a clean, efficiency and productive place that satisfies the needs of its inhabitants. A fundamental aim to the restoration of conditions of equity in the city seems to come from the models of development of sustainable city, related to the improvement of the environment and, above all, to a plan of sustainable society. Leaving from the indications of the European urban policies and those coming from issues about European, Mediterranean and Sicilian experiences, the team of present research may suggest he better political and technological choices adapted to the governance of urban ecosystem (with particular care for the waste, he transports, the management of the water and energetic resources) of the greater Sicilian cities an above all, of those if the Eastern Sicily. They will not come finally neglected the problematic related to the monitoring activities, both in function of the control of the environmental state and that of the continue verify of environmental impact of the pursued choices. Particular attention will be turned to the preventing of the seismic risk.
Keywords: 330